THE IMPORTANCE OF STUDYING ABROAD FOR FOREIGN LANGUAGE ACQUISITION - Oringalieva, Uldaulet; Khan, Shazreena (Журнал иностранных языков и лингвистики, 2025)
The importance of English communication skills has increased with globalization, and governments in various countries have encouraged students to go abroad for studying as well as gaining experiences, explore some differences between culture, education etc. However, the causal impact of studying abroad has rarely been investigated, particularly in non-European countries. Studying abroad for leaning foreign language is transformative experience that brings a wide range of challenges and personal growth opportunities in terms of language learning. As a student living in Malaysia, far from my home country, I have encountered cultural differences, language barriers, and emotional adjustments that have shaped who I am today.